2021
DOI: 10.3390/cancers13122950
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of Circulating T Cell Receptor Repertoire Provides Information about Clinical Outcome after PD-1 Blockade in Advanced Non-Small Cell Lung Cancer Patients

Abstract: Despite the success of immunotherapies in lung cancer, development of new biomarkers for patient selection is urgently needed. This study aims to explore minimally invasive approaches to characterize circulating T cell receptor beta chain (TCR-β) repertoire in a cohort of advanced non-small cell lung cancer (NSCLC) patients treated with first-line pembrolizumab. Peripheral blood samples were obtained at two time points: i) pretreatment (PRE) and ii) first response assessment (FR). Next-generation sequencing (N… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(24 citation statements)
references
References 48 publications
1
9
0
Order By: Relevance
“…A similar trend has been reported in a cohort of renal cell carcinoma patients treated with anti-PD-1 antibodies (32). In contrast, responders among NSCLC patients showed decreased clonality and increased diversity in peripheral blood TCR repertoires after treatment (33,34). Therefore, there is currently no consensus on the characteristics of peripheral blood TCR repertoires associated with therapeutic responses.…”
Section: Tcr Repertoire Analysis In Tumor Immunology: Achievements and Challengessupporting
confidence: 63%
“…A similar trend has been reported in a cohort of renal cell carcinoma patients treated with anti-PD-1 antibodies (32). In contrast, responders among NSCLC patients showed decreased clonality and increased diversity in peripheral blood TCR repertoires after treatment (33,34). Therefore, there is currently no consensus on the characteristics of peripheral blood TCR repertoires associated with therapeutic responses.…”
Section: Tcr Repertoire Analysis In Tumor Immunology: Achievements and Challengessupporting
confidence: 63%
“…Recently, this has included the T-cell receptor (TCR) repertoire of tumour-infiltrating lymphocytes [ 81 83 ]. TCR repertoire diversity in peripheral blood prior to treatment initiation could also represent a predictive biomarker to guide the use of immunotherapy [ 84 , 85 ].…”
Section: Opportunities: Emerging Landscape and Future Clinical Applic...mentioning
confidence: 99%
“…Similarly, the frequency of TRBV6-5 usage was higher in the high-risk group compared with the low-risk group post-RT. In a recent study, high usage of TRBV6-5 in patients with advanced NSCLC was shown to be associated with disease progression and a poor prognosis, and it was also revealed to be a predictive marker of non-durable clinical benefit of anti-PD-1 treatment ( 16 ). Moreover, deep TCR-β sequencing in tissue samples from prostate tumors revealed an abundance of both TRBV6-5 and TRBV6-6 in paracancerous tissue, but not within the tumor ( 17 ).…”
Section: Discussionmentioning
confidence: 99%
“…By contrast, high usage of certain V segments has been associated with a favorable prognosis in several tumor types. Notably, high TRBV20-1 usage in patients with NSCLC has been reported to be associated with improve- ments in both progression-free and overall survival, as well as with an increased response to anti-PD-1 treatment ( 16 ). Taken together, these data may suggest that the preferential usage of specific V gene segments could have an important role in determining the levels and duration of T-cell-mediated antitumor immunity.…”
Section: Discussionmentioning
confidence: 99%